Which Determinants Impact Consumer Purchase Behavior toward Online Purchasing of Organic Food Products? - Pahari, Subhajit; Ghosal, Indrajit; Prasad, Bikram; Dildar, Sayyad Mahejabin (Prabandhan: Indian Journal of Management, 2023)
Organic food products are in higher demand among Indian consumers, although little is known about consumers’ intentions to purchase organic foods online. The purposes of this paper are threefold. First, it attempted to identify and explore the influencing elements of organic food purchases online. Secondly, it assessed the relationship between customers’ buying intention and attitudes concerning organic food; thirdly, it determined how purchase intention or consumption was linked to improved customer health and mental satisfaction. For this study, regular buyers of organic food in India were surveyed using standard structured questionnaires. The data were analyzed using CFA and SEM. Though all five factors positively impacted attitudes toward organic food, perception and health consciousness were identified as the most critical constructs influencing customer attitudes. On the other hand, attitude toward organic food did facilitate consumer buying behavior, which was again highly related to improved health and mental satisfaction of customers. This study contributed to the existing literature by offering theoretical inferences and also offered practical implications. The study’s findings were critical for all organic food stakeholders, as choosing marketing tactics considering customers’ concerns was an essential aspect of identifying a niche for organic food products.